2021
DOI: 10.1177/02761467211042552
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Online Reviews on the Information Flows and Outcomes of Marketing Systems

Abstract: Online reviews are changing the way that consumers shop and firms respond to consumer feedback. Viewed more broadly, online reviews are a type of information flow altering the functioning of marketing systems at the micro, meso, and macro levels. A systematic review of the past two decades of research shows great attention to the impact of online reviews on information flows, as well as the nuances of micro-and meso-level efficiency outcomes. However, there is scant consideration for the effectiveness related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 119 publications
0
5
0
Order By: Relevance
“…Similar implications and questions are likely with technology such as drones or smart speakers. Optimally, consumers need to be given control over their information in the marketing system (Watson and Wu 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Similar implications and questions are likely with technology such as drones or smart speakers. Optimally, consumers need to be given control over their information in the marketing system (Watson and Wu 2022).…”
Section: Discussionmentioning
confidence: 99%
“…An efficient marketing system must innovatively respond to emerging opportunities. A recent systematic review of the marketing literature published between 2000 and 2020 found slight differences between micro- and meso-level efficiency measures (Watson and Wu 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They find that online review analytics can be suitably embedded into analytical models to assess prices, citing the benefits of having access to widely available information from the Internet. Watson and Wu (2022) also explore the impact of online reviews on the information flows and outcomes of marketing systems, observing (p.146) that 'online reviews are changing the way that consumers shop and firms respond to consumer feedback … [and] are an information flow with the potential to change well-being outcomes for all stakeholders, rather than just a tool to be exploited by firms or consumers'. They suggest future research to explore how online reviews and information flows may impact the efficiency and effectiveness of a marketing system.…”
Section: Practical Applications Of Accounting Information System Rese...mentioning
confidence: 99%